CONDITIONS FOR ACHIEVING EFFECTIVE TOURISM DEVELOPMENT IN IRAQ - Z. M. Al-Fahad Anees (Вестник университета)
Current trends in tourism development in Iraq have been considered. Based on the existing problems in the country, a set of measures aimed at developing the tourism industry in Iraq have been proposed, which include: 1) merging strategies for the development of domestic and entry tourism; 2) investing in tourist potential facilities; 3) tourism marketing not only in the major cities of Iraq, but also in the surrounding areas; 4) a system of six necessary steps for the development of tourism, including: acceptance of the tourism industry as a productive sector, presentation of a real picture of tourism in Iraq, coordination of work on tourism with work on environmental conservation, restructuring of the government staff, legislative reforms, setting deadlines for the implementation of strategies. It has been shown that such measures can be applied to the development of various types of tourism, in particular, recreational and religious tourism, which are the most common.